Detecting Lies via a Theme-Selection Strategy - Palena, Nicola (Front Psychol, 2019)
Most of deception research has focused on past events that were either completely truthful or a complete fabrication. However, people often tell a mixture of truths and lies. This could enable investigators to make within-subjects comparisons between different themes discussed in one interview, which we examined in the current experiment. Seventy-three participants took part in the experiment and were asked to either tell the truth about two themes, or to tell the truth about one theme and lie about the second theme in a HUMINT setting. Results showed that examining the differences in the amount of detail provided by the interviewees for each theme- obtained through a Theme-Selection strategy (a within-subjects measure)- yielded stronger results than examining differences between truth tellers and liars based on the entire interview without accounting for themes (between-subjects measure). The present study therefore highlighted the effectiveness of within-subjects measurements to both discriminate truth tellers from liars and to discover which section of a statement is false.